Histopathological Study of Cyclosporine Pulmonary Toxicity in Rats - Said Said Elshama; Ayman El-Meghawry EL-Kenawy; Hosam-Eldin Hussein Osman (Journal of Toxicology)
Cyclosporine is considered one of the common worldwide immunosuppressive drugs that are used for allograft rejection prevention. However, articles that address adverse effects of cyclosporine use on the vital organs such as lung are still few. This study aims to investigate pulmonary toxic effect of cyclosporine in rats by assessment of pulmonary histopathological changes using light and electron microscope examination. Sixty male adult albino rats were divided into three groups; each group consists of twenty rats. The first received physiological saline while the second and third groups received 25 and 40 mg/kg/day of cyclosporine, respectively, by gastric gavage for forty-five days. Cyclosporine reduced the lung and body weight with shrinkage or pyknotic nucleus of pneumocyte type II, degeneration of alveoli and interalveolar septum beside microvilli on the alveolar surface, emphysema, inflammatory cellular infiltration, pulmonary blood vessels congestion, and increase of fibrous tissues in the interstitial tissues and around alveoli with negative Periodic Acid-Schiff staining. Prolonged use of cyclosporine induced pulmonary ultrastructural and histopathological changes with the lung and body weight reduction depending on its dose.